Toxic Effects of Hydroxyl- and Amine-functionalized Silica Nanoparticles (SiO2 and NH2-SiO2 NPs) on Caenorhabditis elegans - Danielle E. Que; Wen-Che Hou; Micah Belle Marie Yap Ang; Chih-Chung Lin (Aerosol and Air Quality Research)
Abstract Silica nanoparticles (SiO2 NPs) are engineered nanomaterials (ENMs) that have a wide range of application. Increased use in manufacturing has led to concerns about their environmental impact and possible adverse health effects. We conducted a comparative toxicity assessment of bare SiO2-NPs and amine-functionalized SiO2 NPs (NH2-SiO2 NPs) utilizing the Caenorhabditis elegans (C. elegans) in vivo model. L1 nematodes were exposed to exposure concentrations of 0.25, 0.5, 2.5, and 5 mg mL−1 until the worms reached the L4 stage. The chronic lethality and lifespan assays revealed a significant decrease in survival rate and lifespan at 2.5 and 5 mg mL−1 for nematodes exposed to bare SiO2 NPs (89% and 88%; 22 days, p < 0.05 and 14 days, p < 0.05) and at 5 mg mL−1 for the NH2-SiO2 NPs-exposed group (86%; 20 days, p < 0.001). Exposure to all SiO2 NP concentrations reduced progeny production to 79–60% while exposure to 2.5 and 5 mg mL−1 of NH2-SiO2 NPs significantly reduced the brood size to 64–63%. Neurobehavioral toxicity was also observed in the SiO2 NP-exposed worms, which displayed significantly decreased head thrashing for up to 92–71% and in the NH2-SiO2 NPs-exposed worms which showed significantly reduced head thrashing movement for up to 91–85% at concentrations of 0.5-5 mg mL−1. Body bending movements were also significantly reduced at 0.5–5 mg mL−1 SiO2 NPs (71–34%) and 2.5–5 mg mL−1 NH2-SiO2 NPs (94–66%). Significant shortening of body size was also observed in nematodes exposed to 0.5–5 mg mL−1 for both SiO2 NPs (93–81%) and NH2-SiO2 NPs (94–88%). Overall, bare SiO2 NPs were observed to be more toxic due to the negatively charged surface OH groups, which may have disrupted protein homeostasis, resulting in the observed toxicities. We suggest that functionality is an important indicator in nanosafety evaluations.